Reading Literacy Model Based Tri Hita Karana for Student's Thinking Skills - Ni Ketut Desia Tristiantari; Dadang Sunendar; Tatat Hartati; Isah Cahyani (Universitas Pendidikan Ganesha, 2023)
Critical thinking skills are fundamental skills in 21st-century learning. One of these skills is influenced by students' reading literacy. However, reading literacy activities in elementary schools have yet to be maximized. This study aimed to analyze teachers' needs in elementary school learning and produce a prototype of the Tri Hita Karana Reading Literacy model. This type of research is research and development (RnD). The research and development model design used was adapted from Borg and Gall's theory. The subjects involved were 55 teachers in the preliminary study, 6 people, and 2 practitioners for the product feasibility test. Methods of data collection for preliminary study are using a questionnaire. Data were analyzed using quantitative descriptive analysis techniques. The research results show that teachers must develop a model to maximize students' literacy activities. Second, the average calculation of the validator's assessment results is 4.3, which means it is in the very good category, with an average number of content aspects of 4.3, layout and design aspects of 4.2, and grammar of 4,4. These results indicate that the THK Literacy Model is considered to have met the validity criteria. The conclusion of the experts regarding the development of this model is that the model can be used with several revisions.